Effects of Mesenchymal Stem Cell Transplantation in Combination with Heparin on Acute Myocardial Infarction in a Rabbit Model - Hajigol, Shahrzad; Moradi Gardeshi, Tohid; Safizadeh, Fahimeh; Khosh Ravesh, Roya; Abbasi, Mojtaba (Archives of Medical Laboratory Sciences, 2021)
Background and Aim: Background: Stem cell transplantation, combined with some bioactive substances, has revealed promising outcomes in treating cardiac tissue damage caused by myocardial infarction (MI). In the present study, we evaluated the beneficial consequence of mesenchymal stem cells (MSCs) transplantation combined with heparin on heart damage within infarcted rabbits. Methods: Twenty-eight male New Zealand white rabbits were randomly distributed into four groups: control, MI, MI+ MSCs, and MI+MSCs+ heparin. Functional parameters of the left ventricle through echocardiography, lesion area through Macro trichrome evaluation, and angiogenesis through Masson's trichrome staining were compared between groups. Results: Ejection fraction and fractional shortening were improved in MI +MSCs and MI+ MSCs + heparin group compared to the MI group (P<0.05). The lesion area was significantly reduced, and angiogenesis was markedly increased in MI +MSC + heparin treated animals compared to MI and MI +MSCs groups. Conclusion: Although MSCs injection to infarcted area restored normal heart function, we concluded that in the infarcted region of animals, MSCs injection combined with exogenous heparin could have more effects on the left ventricle functional parameters, cardiac lesions, and new vessel formation. *Corresponding Author: Roya Khosh Ravesh; Email: Khoshraveshroya82@gmail.com Please cite this article as: Hajigol S, Moradi Gardeshi T, Safizadeh F, Khosh Ravesh R, Abbasi M. Effects of Mesenchymal Stem Cell Transplantation in Combination with Heparin on Acute Myocardial Infarction in a Rabbit Model. Arch Med Lab Sci. 2021;7:1-9 (e19). https://doi.org/10.22037/amls.v7.34932